2015
DOI: 10.1093/jnci/djv310
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Response of BRAF V600E Mutant Papillary Craniopharyngioma to Targeted Therapy

Abstract: We recently reported that BRAF V600E is the principal oncogenic driver of papillary craniopharyngioma, a highly morbid intracranial tumor commonly refractory to treatment. Here, we describe our treatment of a man age 39 years with multiply recurrent BRAF V600E craniopharyngioma using dabrafenib (150mg, orally twice daily) and trametinib (2mg, orally twice daily). After 35 days of treatment, tumor volume was reduced by 85%. Mutations that commonly mediate resistance to MAPK pathway inhibition were not detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
160
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(166 citation statements)
references
References 16 publications
6
160
0
Order By: Relevance
“…BRAF inhibitors, including vemurafenib and dabrafenib, have proved successful either alone or in conjunction with trametinib, an inhibitor of another MAPK member MEK, to treat adults with papillary craniopharyngioma, resulting in tumor shrinkage with good tolerability [2,5,24,25]. In addition, increasing pediatric data is emerging for BRAF and MEK inhibitors in the treatment of surgically inaccessible gliomas that express BRAF V600E mutations, with an acceptable side effect profile in this age group [1,3,4,16,18,29].…”
Section: Discussionmentioning
confidence: 99%
“…BRAF inhibitors, including vemurafenib and dabrafenib, have proved successful either alone or in conjunction with trametinib, an inhibitor of another MAPK member MEK, to treat adults with papillary craniopharyngioma, resulting in tumor shrinkage with good tolerability [2,5,24,25]. In addition, increasing pediatric data is emerging for BRAF and MEK inhibitors in the treatment of surgically inaccessible gliomas that express BRAF V600E mutations, with an acceptable side effect profile in this age group [1,3,4,16,18,29].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of BRAF V600E mutations in the blood of patients with PCP highlights the potential of identifying CTNNB1 mutations in cfDNA of ACP patients, therefore facilitating less invasive diagnostic testing, residual disease assessment, and risk stratification. 8 Similarly, highlighting the potential for novel approaches for disease monitoring, it has been reported that urinary levels of matrix metalloproteinases were raised in a girl with recurrent ACP and subsequently became normalized following resection of the tumor. 48 Detailed proteomic analyses of cystic fluid, or even lipidomic and metabolomics analyses, could lead to the characterization of a profile unique for ACP, which could help both diagnosis and monitoring of treatment response.…”
Section: Methodologies Used To Understand the Molecular Pathology Of Acpmentioning
confidence: 97%
“…6,8,9 In contrast, for adamantinomatous craniopharyngioma (ACP), while mutations in the gene CTNNB1 have been identified in the majority of cases, no such "magic bullet" treatments have been translated into the clinic yet. In this review we summarize recent advances in the understanding of ACP pathology and discuss how this might impact practice in the future.…”
mentioning
confidence: 99%
“…Importantly, after therapy was halted for a CSF leak associated with tumor shrinkage, tumor recurrence occurred within 6 weeks and long-term control was not achieved after therapy was restarted. In a 39-year-old patient with multiply recurrent PCP, who had required 4 craniotomies and an endonasal resection for multiple cystic recurrences, Brastianos and collegues 6 reported an excellent initial response to combination therapy using the RAF inhibitor dabrafenib and MEK inhibitor trametinib (Fig. 3).…”
Section: Brafmentioning
confidence: 99%